2021
DOI: 10.1177/13591053211030994
|View full text |Cite
|
Sign up to set email alerts
|

The moderated associations of self-compassion with physiological and psychological stress responses: Comparisons between cancer caregivers and non-caregivers

Abstract: Self-compassion has been shown to be protective against stress. Whether its stress buffering effect differs between cancer caregivers and non-caregivers is unknown. This study examined the moderating effect of self-compassion among cancer caregivers relative to non-caregivers by recruiting cancer caregivers from the hospital and a community sample matching on sex and age. Participants completed a questionnaire which comprised the self-reported anxiety (STAI-6) and self-compassion (SCS-SF) measures, and adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The links between affect and diurnal cortisol pattern in cancer patients (Castonguay et al, 2017;Wang & Hoyt, 2018) suggest a potential mediating role for affect between self-compassion and diurnal cortisol pattern. A recent study (Chan et al, 2021) has found moderating effects of selfcompassion against anxiety symptoms but not physiological stress in cancer caregivers.…”
mentioning
confidence: 96%
“…The links between affect and diurnal cortisol pattern in cancer patients (Castonguay et al, 2017;Wang & Hoyt, 2018) suggest a potential mediating role for affect between self-compassion and diurnal cortisol pattern. A recent study (Chan et al, 2021) has found moderating effects of selfcompassion against anxiety symptoms but not physiological stress in cancer caregivers.…”
mentioning
confidence: 96%